Education plays a greater role than age in cognitive test performance among participants of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Issue 1 (December 2015) - de Azeredo Passos, Valéria; Giatti, Luana; Bensenor, Isabela; Tiemeier, Henning; Ikram, M.; de Figueiredo, Roberta; Chor, Dora; Schmidt, Maria; Barreto, Sandhi
Abstract Background Brazil has gone through fast demographic, epidemiologic and nutritional transitions and, despite recent improvements in wealth distribution, continues to present a high level of social and economic inequality. The ELSA–Brasil, a cohort study, aimed at investigating cardiovascular diseases and diabetes, offers a great opportunity to assess cognitive decline in this aging population through time-sequential analyses drawn from the same battery of tests over time. The purpose of this study is to analyze the influence of sex, age and education on cognitive tests performance of the participants at baseline. Methods Analyses pertain to 14, 594 participants with aged 35 to 74 years, who were functionally independent and had no history of stroke or use of neuroleptics, anticonvulsants, cholinesterase inhibitors or antiparkinsonian agents. Mean age was 52.0 ± 9.0 years and 54.2 % of participants were women. Cognitive tests included the word memory tests (retention, recall and recognition), verbal fluency tests (VFT, animals and letter F) and Trail Making Test B. Multivariable linear regression analysis was used to determine the influence of sociodemographic characteristics on the distribution of the final score of each test. Results Women had significant and slightly higher scores than men in all memory tests and VFT, but took more time to perform Trail B. Reduced performance in all tests was seen with an increase age and, more importantly, with decrease level of education. The word list and VFT scores decreased at about one word for every 10 years of age; whereas higher-educated participants scored four words more on the word list test, and six or seven more correct words on VFT, when compared to lower-educated participants. Additionally, the oldest and less educated participants showed significant lower response rates in all tests. Conclusions The higher influence of education than age in this Brazilian population reinforce the need for caution in analyzing and diagnosing cognitive impairments based on traditional cognitive tests and the importance of searching for education-free cognitive tests, especially in low and middle-income countries.